2021
DOI: 10.2106/jbjs.oa.21.00023
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Orthopaedic Resident Case Logs to Identify Fluctuations in Exposure to Adult Orthopaedic Procedures

Abstract: Introduction:Orthopaedic surgery resident case exposure is an important component of surgical training and is monitored by the Accreditation Council for Graduate Medical Education (ACGME) to ensure resident readiness for graduation. The purpose of this study was to investigate trends in exposure to adult orthopaedic surgical procedures and analyze the impact of the 2013 update in ACGME case logging expectations.Methods:A retrospective review of ACGME case log data was conducted for adult orthopaedic procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…12 Orthopaedic residency directors have expressed concerns about the negative impact of COVID-19 on training. 13,20 Education has also suffered through the cancellation of conferences and courses; online teaching has become commonplace during the pandemic, but both our study and others have found satisfaction with this is lower than traditional in-person teaching. 21 The issue of surgeon burnout has received significant attention in recent years.…”
Section: Discussionmentioning
confidence: 56%
“…12 Orthopaedic residency directors have expressed concerns about the negative impact of COVID-19 on training. 13,20 Education has also suffered through the cancellation of conferences and courses; online teaching has become commonplace during the pandemic, but both our study and others have found satisfaction with this is lower than traditional in-person teaching. 21 The issue of surgeon burnout has received significant attention in recent years.…”
Section: Discussionmentioning
confidence: 56%
“…Multiple studies have analyzed resident exposure and shoulder procedure log reporting before and after the implementation of case minimums, and several of which have identified a decrease in resident-reported arthroscopic case volumes. 2 , 10 , 14 , 21 , 25 While the indication for these procedures is not provided by the ACGME data sets, this may be due to the shifting of the limited opportunities during the pandemic from residents to fellows, as they generally have less time allotted to develop mastery of a difficult visuospatial skill. 6 , 9 Prior to 2019-2020 academic year, orthopedic sports medicine fellows performed approximately 275% more shoulder ( P <.0001) surgeries than residents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have previously evaluated the trends of resident and early surgeon-reported shoulder case volumes, 2 , 3 , 7 , 8 , 14 , 16 , 17 , 20 , 21 but there is a paucity of literature analyzing the breadth of shoulder case logs since case log reporting inception or the effect of the coronavirus disease 2019 (COVID-19) pandemic. Our objective is to analyze the 16 years of ACGME-reported shoulder case log data and to assess the impact of the COVID-19 pandemic on resident shoulder case log volumes.…”
mentioning
confidence: 99%
“…Finally, case volume data are self-reported and susceptible to coding inaccuracies and misrepresentation. [23][24][25][26][27] However, given its effect on the accreditation process, case logs are routinely monitored by faculty and accreditation bodies in orthopaedic surgery resident education on a regular basis.…”
Section: Figurementioning
confidence: 99%